1985
DOI: 10.1111/j.1475-2743.1985.tb00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing nitrogen inputs and outputs in two Scottish upland catchments

Abstract: The factors influencing inorganic nitrogen inputs in wet deposition in two upland catchments in northeast Scotland are discussed. Seasonal trends in nitrate-nitrogen concentrations in water draining from the catchments, and in monthly nitrate-nitrogen outputs, are reported and explained. The inputs in rain exceeded the output in the rivers in the two catchments by 3.9-9.4 kg ha-la-'. Retention by vegetation probably plays a crucial role in nitrogen cycling in the uplands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 25 publications
0
6
2
1
Order By: Relevance
“…NO 3 -is often immobilized by microbial and plant uptake during the warmer months, while biological uptake and transformation of NO 3 -is highly reduced during the colder months due to the weaker ability of retaining NO 3 - (Black et al 1993;Edwards et al 1985;Balestrini et al 2013). However, in our data, no similar variation in concentrations was observed during different reasons.…”
Section: Spatial Distributions Of N Fractionscontrasting
confidence: 74%
“…NO 3 -is often immobilized by microbial and plant uptake during the warmer months, while biological uptake and transformation of NO 3 -is highly reduced during the colder months due to the weaker ability of retaining NO 3 - (Black et al 1993;Edwards et al 1985;Balestrini et al 2013). However, in our data, no similar variation in concentrations was observed during different reasons.…”
Section: Spatial Distributions Of N Fractionscontrasting
confidence: 74%
“…Such studies have revealed distinct seasonal patterns of DOC and N release, with concentrations of DOC and DON displaying summer maxima and winter minima, and vice versa for NO 3 -N. The patterns for DOC and DON are generally explained by enhanced turnover and release of soluble 623 organic matter in soils (Grieve, 1984) and surface waters (Chapman et al, 2001) respectively during the warmer summer months, whereas the pattern for NO 3 -N reflects the seasonal availability of NO 3 -N in the soil for leaching, which is significantly reduced during the summer by biological uptake (Edwards et al, 1985). However, soil type and drainage status can influence these trends, since DOC may be removed from solution by adsorption in sesquioxide-rich mineral horizons (Jardine et al, 1989;Kennedy et al, 1996), and NO 3 -N may not be produced in waterlogged profiles, due to the effects of anaerobia (Rangely and Knowles, 1988;Adamson et al, 1998).…”
Section: Introductionmentioning
confidence: 91%
“…As a consequence, once deposition exceeds 10-16 kg N ha −1 yr −1 , retention of this N by the vegetation will cease. Although N concentrations in Calluna litter suggest that the litter layer can contribute to N retention, especially of NO − 3 (Edwards et al, 1985), according to Black et al (1993), peats in particular, but also moorlands, are the least likely semi-natural ecosystems to retain N.…”
Section: How Does the Vegetation Respond To N?mentioning
confidence: 99%